Reproductive diseases in a small dairy farm and its importance in regional development (Research, Society and Development, 2020)
Losses due to low reproductive efficiency can economically affect production in a small dairy farm. The aim of this study was to detect the presence of anti-Leptospira, anti-Toxoplasma gondii, and anti-Neospora caninum antibodies in dairy cows with history of reproductive problems at a small dairy farm in Umuarama, Paraná, Brazil. The evaluated herd presented with history of abortion and return to estrus. Of the 37 samples analyzed, 10 (27%) were positive in microscopic serum agglutination, with titers ranging from 100 to 400, 21 (56.75%) were positive for Toxoplasma gondii in the indirect immunofluorescence test (IIFT), with titers ranging from 16 to 256, and four (10.8%) were positive for Neospora caninum in IIFT, with titers ranging from 25 to 50. No variables were associated with any infection. Leptospirosis, toxoplasmosis, and neosporosis are widespread in herds and may have a negative impact on reproductive parameters of dairy cattle. Periodic serological evaluations are important, as they may guide the choice of preventive disease control measures in the herd and also alert and educate small producers and the local population on the possible presence of zoonoses spread by these infectious agents, in addition, it can be concluded that infectious diseases can have negative implications on the reproductive parameters of dairy cattle causing return to heat and abortion.